2017
DOI: 10.1186/s12944-017-0546-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of orange (Citrus sinensis L.) peel aqueous extract and hesperidin on oxidative stress and peptic ulcer induced by alcohol in rat

Abstract: BackgroundMassive alcohol drinking can lead to gastric ulcer. In the present study we investigated the gastroprotective effect of Citrus sinensis peel aqueous extract (CSPE) and Hesperidin (H) in ethanol (EtOH) induced oxidative stress and peptic ulcer in rats.MethodsSeventy adult male Wistar rats were divided into seven groups of 10 each: control, EtOH (4 g/kg b.w.), EtOH + various doses of CSPE (100, 200 and 400 mg/kg, b.w.), EtOH + Hesperidin (50 mg/kg, p.o.) and EtOH + Omeprazole (OM, 20 mg/kg, p.o.). Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Duodenal ulcer (DU) is one of the major gastrointestinal disorders, which affects annually approximately 10-15% of the population worldwide [1]. DU occurs due to loss of balance between offensive and defensive factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duodenal ulcer (DU) is one of the major gastrointestinal disorders, which affects annually approximately 10-15% of the population worldwide [1]. DU occurs due to loss of balance between offensive and defensive factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, serious attention has been paid to natural products, owing not only to its favorable safety profile and relatively low cost but also to its attracting efficacy, minimal postprandial untoward effects, and superior compatibility with human body system. With regard to DU therapies, various research studies have shown potential gastroprotective activities of plant-based extracts and TCM formulas, such as Citrus sinensis [1], Melastoma malabathricum [4], Spondias mombin [5], and Xiao Chaihu decoction [6].…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the upregulation of the Nrf2 gene expression which enhances antioxidant enzymes activity, thus decreasing oxidative stress (Parhiz, Roohbakhsh, Soltani, Rezaee, & Iranshahi, ). The positive antioxidant capacity of hesperidin had been previously described for production animals, such as poultry (orange peel 0.04%—Akbarian, Golian, Kermanshahi, Smet, & Michiels, ; hesperidin 0.002%—Ognik, Cholewińska, Sembratowicz, Grela, & Czech, ) and laying hens (0.05% hesperidin—Iskender et al, ), and also for rats (0.04% orange peel aqueous extract—Selmi, Rtibi, Grami, Sebai, & Marzouki, ). Further studies assessing hesperidin, reactive oxygen metabolites and the biological antioxidant potential could help in understanding OPF on Nile tilapia antioxidant capacity.…”
Section: Discussionmentioning
confidence: 78%
“…Citrus sinensis (L.) Osbeck (Rutaceae), commonly known as the sweet orange, is ubiquitous in human diet across the world (Lv et al, 2015) and belongs to the citrus family (Duarte et al, 2016). C. sinensis peel is a rich source of phenolic compounds, with antidiabetic, antioxidant, and free radical scavenging activities, effects against gastrointestinal illnesses, and potential protection against different cancers and cardiovascular disorders (Rotelli et al, 2003;Selmi et al, 2017). A number of recent experiments have explored the therapeutic potential of phenolics derived from citrus species as a single bioactive molecule (Selmi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…C. sinensis peel is a rich source of phenolic compounds, with antidiabetic, antioxidant, and free radical scavenging activities, effects against gastrointestinal illnesses, and potential protection against different cancers and cardiovascular disorders (Rotelli et al, 2003;Selmi et al, 2017). A number of recent experiments have explored the therapeutic potential of phenolics derived from citrus species as a single bioactive molecule (Selmi et al, 2017). C. sinensis peel exhibits hypoglycaemic and hypolipidaemic effects in an alloxan-induced animal model of type 1 diabetes (Luka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%